Inhibition of autophagy promotes apoptosis and enhances anticancer efficacy of adriamycin via augmented ROS generation in prostate cancer cells. (August 2016) - Wang, Jizhong; Tan, Xiangpeng; Yang, Qi; Zeng, Xiangfeng; Zhou, Yuying; Luo, Wu; Lin, Xiaomian; Song, Li; Cai, Jialong; Wang, Tianxiang; Wu, Xiaoping
Graphical abstract: Highlights: ADM inhibits cell viability and enhances apoptosis of prostate cancer cells. ADM induces protective autophagy via PI3K/Akt(T308)/mTOR cascade. Autophagy inhibition increases ADM-induced apoptosis and enhances chemosensitivity. Blockade of autophagy augments ROS generation induced by ADM. ROS serves as a mediator directing the modulation effect of autophagy on apoptosis. Abstract: The interplay between autophagy and apoptosis response to chemotherapy is still a subject of intense debate in recent years. More efforts have focused on the regulation effects of apoptosis on autophagy, whereas how autophagy affects apoptosis remains poorly understood. In this study performed on prostate cancer cells, we investigated the role of autophagy in adriamycin-induced apoptosis, as well as the mechanisms mediating the effects of autophagy on apoptosis response to adriamycin (ADM). The results show that ADM not only inhibited cell viability and enhanced apoptosis, but also promoted autophagy via PI3K/Akt(T308)/mTOR signal pathway. Inhibition of autophagy by either pharmacological inhibitor chloroquine (CQ) or RNA interference of Atg5 increased ADM-induced apoptosis and enhanced the chemosensitivity of prostate cancer cells. Moreover, blockade of autophagy augmented reactive oxygen species (ROS) generation induced by ADM. Scavenging of ROS by antioxidant N -acetyl-cysteine (NAC) reversed the strengthened effects of CQ on ADM-induced apoptosis and rescued the cells from apoptosis. The results identified ROS as a potential mediator directing the modulation effects of the protective autophagy on apoptosis response to ADM. Suppression of the protective autophagy might provide a promising strategy to increase the anticancer efficacy of agents in the treatment of prostate cancer.